Enriched environment-induced neuroplasticity in ischemic stroke and its underlying mechanisms - Han, Ping-Ping; Han, Yu; Shen, Xin-Ya; Gao, Zhen-Kun; Bi, Xia (Frontiers in Cellular Neuroscience, 2023)
Stroke is a common cerebrovascular disease that can interrupt local blood flow in the brain, causing neuronal damage or even death, resulting in varying degrees of neurological dysfunction. Neuroplasticity is an important neurological function that helps neurons reorganize and regain function after injury. After cerebral ischemia, neuroplasticity changes are critical factors for restoring brain function. An enriched environment promotes increased neuroplasticity, thereby aiding stroke recovery. In this review, we discuss the positive effects of the enriched environment on neuroplasticity after cerebral ischemia, including synaptic plasticity, neurogenesis, and angiogenesis. In addition, we also introduce some studies on the clinical application of enriched environments in the rehabilitation of post-stroke patients, hoping that they can provide some inspiration for doctors and therapists looking for new approaches to stroke rehabilitation.